2023
DOI: 10.1039/d2ra07791d
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance, oxidation resistance and flexible Zn@MXene/cellulose nanofibers electromagnetic shielding film

Abstract: This work focuses on studying the excellent oxidation resistance performance and flexibility of electromagnetic shielding materials, greatly promoting the practical application in marine engineering, wearable field and electronic packaging field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The oxidation of MXene under high‐temperature and humid environments can be prevented by introducing positive metal ions on the MXene nanosheets because metal ions readily bond with oxygen‐containing groups. Compared to Ag and Ni, Zn has higher reactivity, [ 22 ] less deformability, better flexibility, and higher transparency. [ 23 , 24 ] To utilize Ti 3 C 2 T x MXene as an FTCE, we sandwiched a thin Ag layer between the MXene layers and achieved a window of WF ranging from 4.61 to 5.08 eV, which provided positive and negative changes in the WF of the MXene.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of MXene under high‐temperature and humid environments can be prevented by introducing positive metal ions on the MXene nanosheets because metal ions readily bond with oxygen‐containing groups. Compared to Ag and Ni, Zn has higher reactivity, [ 22 ] less deformability, better flexibility, and higher transparency. [ 23 , 24 ] To utilize Ti 3 C 2 T x MXene as an FTCE, we sandwiched a thin Ag layer between the MXene layers and achieved a window of WF ranging from 4.61 to 5.08 eV, which provided positive and negative changes in the WF of the MXene.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a film composed of elastomer/MXene nanocomposites with a thickness of 1 mm exhibited an EMI SE of 49 dB at a MXene volume fraction of 19.6% . Similarly, a film incorporating 12 μm Zn@MXene/cellulose nanofibers demonstrated an EMI SE of 60.3 dB …”
Section: Introductionmentioning
confidence: 95%
“…21 Similarly, a film incorporating 12 μm Zn@MXene/cellulose nanofibers demonstrated an EMI SE of 60.3 dB. 22 Li et al increased the MXene content up to 90 wt % in PVDF 23 and obtained an EMI SE of 42 dB at a thickness of 17 μm. Interestingly, the shielding value of pure MXene film is always much higher when compared to that of >80 wt % fillerbased polymer composites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Increasing the cellulose layer can also increase the toughness of MXene/cellulose composite materials [49] . Furthermore, a study has shown that MXene/cellulose‐based composite materials can withstand up to 100 bending cycles, which had no detrimental effect on practical applications [50] . As a result, it is also anticipated that the toughness, flexibility, durability, and rheological properties of MXene/cellulose‐based composite electrodes will also improve.…”
Section: Introductionmentioning
confidence: 99%
“…[49] Furthermore, a study has shown that MXene/cellulose-based composite materials can withstand up to 100 bending cycles, which had no detrimental effect on practical applications. [50] As a result, it is also anticipated that the toughness, flexibility, durability, and rheological properties of MXene/cellulose-based composite electrodes will also improve. However, very few studies have been found that discuss MXene/cellulose-based composites.…”
Section: Introductionmentioning
confidence: 99%